Solutions of Natural Convection of Nanofluids in a Parallelogrammic Enclosure by Finite Difference Method - Habibis Saleh; Sri Basriati; Ishak Hashim (Institut Teknologi Bandung, 2011)
Detailed numerical calculations for heat transfer enhancement utilizing nanofluids in a parallelogrammic enclosure are presented in this paper. The sloping walls are maintained isothermally at different temperatures. The top and bottom horizontal straight walls are kept adiabatic. To simplify the effort in matching the grid mesh with the sloping walls of the parallelogram, the computational domain is mapped onto a rectangular shape using a non-linear axis transformation. Transport equations are modeled by a stream-vorticity formulation and are solved numerically by finite difference method. Based upon the numerical predictions, the effect of the base angle of the parallelogrammic enclosure on flow and temperature pattern and the heat transfer rate within the enclosure are presented. Increasing the base angle was found to decrease the heat transfer rate. Keywords: Numerical method, Natural convection, Nanofluids. Â Solusi Konveksi Alami Fluida Nano dalam Bangun Jajaran Genjang Tertutup Menggunakan Metode Elemen Hingga Abstrak Dalam makalah ini disajikan perhitungan numerik secara rinci untuk permasalahan peningkatan perpindahan kalor memanfaatkan fluida nano dalam bangun jajarangenjang tertutup. Kedua sisi miring jajarangenjang tersebut dipertahankanÂ isotermal pada suhu yang berbeda. Sisi atas dan bawahnya dipertahankan dalam keadaan adiabatik. Untuk menyederhanakan usaha dalam menyesuaikan jaring-grid dengan sisi-sisi miring jajarangenjang, domain komputasi dipetakan ke bentuk persegi panjang menggunakan transformasi sumbu tidak linear. Persamaan-persamaan transport dimodelkan dengan rumus aliran-pusaran dan diselesaikan menggunakan metode beda hingga. Berdasarkan prediksi numerik, pengaruh dari sudut dasar jajarangenjangÂ pada pola aliran dan suhu dan juga tingkat perpindahan kalor dalam jajarangenjang disajikan. Disimpulkan bahwa pembesaran sudut dasar jajarangenjang didapati menurunkan tingkat perpindahan kalor. Kata kunci: Metode numerik, Konveksi alami, Fluida nano.